The Typology of Authority in Islam (Analysis of the views of the Islamic community In Indonesia about Ulil Amri in the Determination of the Beginning of Hijri Months) - Musonif, Ahmad (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract The diversity of Muslims in Indonesia is accompanied by a diversity of paradigms causing Muslims to be divided into several diverse communities. This community is in the form of religious organizations, congregations, or certain recitals. Each community of Muslims has various views regarding Ulil Amri or religious authority. Based on the typology, religious authority in Indonesia can be divided into Rational Legal, Substantive, Charismatic, and Traditional authorities. The acceptance factor of a community towards a certain authority is based on a rational factor based on religious or community values and also an effective factor. In addition, the competence of the authorities is also a factor in his acceptance as the party followed by his orders. Keywords: The Typology Of Authority, The Islamic Community, The Ulil Amri, Hijri Month. Abstrak Keberagaman umat Islam di Indonesia disertai dengan keberagaman paradigmanya menyebabkan umat Islam terbagi-bagi dalam beberapa komunitas yang beragam. Komunitas ini dalam berbentuk organisasi keagamaan, Jamaah tarekat, ataupun jamaah pengajian tertentu. Masing-masing komunitas umat islam ini memiliki pandangan yang beragam terkait Ulil Amri atau pemangku otoritas keagamaan. Berdasarkan tipologinya otoritas keagamaan di Indonesia dapat dibagi menjadi otoritas Rasional Legal, Rasional Substantif, Kharismatik, dan Tradisional. Faktor penerimaan (acceptance) suatu komunitas terhadapemangku otoritas tertentu didasarkan pada faktor rasional berbasis nilai agama atau komunitas dan juga faktor afektif. Selain itu kompetensi pemangku otoritas juga menjadi faktor diterimanya sebagai pihak yang diikuti perintahnya. Kata Kunci : Typologi Otoritas, Komunitas Islam, Ulil Amri, Bulan Hijriah.